Poster:A Contactless Health Monitoring System for Humans and Animals - Song, Yingjian; Pitafi, Zaid Farooq; Zeng, Zixuan; Chen, Jiayu; Zhang, Yida; Phillips, Bradely; Brainard, Benjamin M; Song, WenZhan (Proceedings of the ... International Conference on Embedded Networked Sensor Systems. International Conference on Embedded Networked Sensor Systems, 2024)
Health monitoring is essential for both humans and animals in daily life. While numerous health monitoring systems have been developed, the majority are designed exclusively for either humans or animals, and most require direct physical contact. We have developed BedDot, a contactless health monitoring system for both humans and animals using a seismic sensor. BedDot can be deployed in various environments, such as bed and seat settings for humans, as well as in cages for animals, to monitor occupancy, heart rate (HR), respiratory rate (RR), and blood pressure (BP). Our system demonstrates high accuracy in the clinical experiments of 150 patients and 16 dogs and cats.